PENGARUH KONTINUITAS SANTRI DALAM MUROJA’AH TERHADAP KUALITAS HAFALANNYA PADA AL-QUR’AN: (Studi Analisis di Kelas V Pondok Pesantren Nurus Sunnah Tegal) - Teguh Pramono; Taufiq Fauzan Ginanjar (Berajah Journal, 2026)
This study aims to determine the effect of students’ continuity in performing muroja’ah on the quality of Qur’anic memorization among fifth-grade students at Pondok Pesantren Nurus Sunnah Tegal. The background of this research is the variation in memorization quality among students despite having relatively similar amounts of memorized verses. This study employs a quantitative approach using a correlational method. Data were collected through observation, questionnaires, and memorization tests. The results indicate that there is a significant effect of muroja’ah continuity on the quality of Qur’anic memorization. The more consistent the students perform muroja’ah, the higher the quality of their memorization, as reflected in fluency, accuracy of tajwid, and memorization retention. This research is expected to serve as a reference for Qur’anic educational institutions in improving students’ memorization quality through continuous and structured muroja’ah practices.